Pengaruh Kampanye Hijau “Bring Back Our Bottles” terhadap Citra Merek (Studi Kasus Pada Konsumen The Body Shop di Kota Bandung) - Rahman, Silvie Monica; Nurtjahjadi, Edi (J-MAS (Jurnal Manajemen dan Sains), 2024)
Indonesia is the second largest producer of marine plastic waste in the world with 187.2 million tons of waste. The beauty industry worldwide produces more than 120 billion packages every year. The rate of the beauty industry is increasing every year and in 2023 it increased by 4.75% and is predicted to continue to increase until 2027. However, there was a decrease in The Body Shop index, in 2021 by 5.6% then in 2022 by 3.7% and finally in 2023 by 3.2%. This indicates a decrease in The Body Shop brand image. The purpose of this study is to determine the effect of the "Bring Back Our Bottles" green campaign on The Body Shop brand image. The data collection technique used is non probability sampling with purposive sampling research with a total of 90 respondents who have bought or used The Body Shop in Bandung City aged 17 years and over. Empirical data in this study were collected using a one shoot study approach and then processed and analyzed using simple regression using SPSS version 26. The results showed that the "Bring Back Our Bottles" green campaign had a positive effect on brand image. Therefore, the management of The Body Shop can prioritize to improve all indicators that make up the green campaign because it is expected to have a positive impact on brand image.